Active learning: Challenges for the information professional - Olivera, Iliana Artiles; Jacomino, Carlos Alexander Mendoza; Paz, Dianelys Martínez (Advanced Notes in Information Science, 2024)
Active learning in continuing education empowers reflective teachers who practice new knowledge and skills in order to develop future information professionals, long-term memories, and deeper understanding; connect different ideas with each other; and think creatively. The Information Sciences career of the Universidad Central “Marta Abreu” de Las Villas in this endeavor and in the activity of continuing education for teachers aims to design learning situations in continuing education actions for teachers who train information professionals. These situations are linked to active learning, considering the experience as an opportunity to learn and integrate it into their performance as innovative teachers. The qualitative methodology followed the course of the pedagogical experience and was based on discussion groups with teachers. The course, which was implemented as a function of continuing education, showed that participants integrated experiences based on active methodologies into their daily classroom practice. This integration facilitated the training of thinking to create and rethink ideas, using imagination, creativity, strategic and ethical, critical and constructive reflection within the innovation processes. Additionally, it awakened the willingness to learn, to risk, and to face uncertainty. Active learning situations achieved controversy, agreement and/or disagreement, and the satisfaction of an innovative teacher.